The Brasilia Experiment : Road Access and the Spatial Pattern of Long-term Local Development in Brazil - Bird, Julia; Straub, Stephane (World Bank Group, Washington, DC, 2014)
This paper studies the impact of the rapid expansion of the Brazilian road network, which occurred from the 1960s to the 2000s, on the growth and spatial allocation of population and economic activity across the country's municipalities. It addresses the problem of endogeneity in infrastructure location by using an original empirical strategy, based on the "historical natural experiment" constituted by the creation of the new federal capital city Brasília in 1960. The results reveal a dual pattern, with improved transport connections increasing concentration of economic activity and population around the main centers in the South of the country, while spurring the emergence of secondary economic centers in the less developed North, in line with predictions in terms of agglomeration economies. Over the period, roads are shown to account for half of pcGDP growth and to spur a significant decrease in spatial inequality.